The two-year survival rate of laryngeal squamous cell carcinoma patients treated at Dr. George Mukhari academic hospital South Africa - Muanza, Dikamba; Kotu, Monica; Olwoch, Ian Paul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: The study was conducted to assess the outcome of patients diagnosed with laryngeal squamous cell carcinoma (LSCC) treated at a tertiary level hospital in South Africa. The focus was the two-year disease-specific survival (DSS) rate after diagnosis as a measuring tool for the outcomes of the disease. Methods: A retrospective cross-sectional descriptive study was conducted at Dr. George Mukhari academic hospital (DGMAH) from 1 January 2010 to 31 December 2015. The data was collected from files of patients who were identified by clinical laryngeal symptoms, pan-endoscopy and biopsy. A total of 37 files of patients diagnosed as LSCC were included in the study. Results: 166 hospital records were retrieved. After application of inclusion and exclusion criteria, the study excluded 129 files because of benign lesions, malignancies other than SCC on histology report, SCC from upper aero-digestive sites other than the larynx or files with incomplete information. Therefore, 37 recordswere considered for the study. Conclusions: The study found the two-year DSS to be 43.2%. A significant contributing factor to the low two-year DSS was the advanced stage of the disease (III and IV) at the time of the presentation that was managed by palliative treatment. Advanced disease was likely due to delayed presentation to the hospital influenced by a low level of patient health knowledge, the negative impact of religious and cultural beliefs, low disposable household income coupled with high distance from home to the nearest hospital, and suboptimal screening at the primary health care level.